Increased Landslide Disaster Preparedness of Dukuh Kerajan Community, Tulungagung Regency Through Poster Media - Aulady, Mohamad Ferdaus Noor; Akbar, Yafie Abdillah (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
Landslide disasters in Indonesia are increasing, one of which is in Tulungagung Regency, East Java Province, including areas that are quite vulnerable to landslides. It was recorded that 55 landslides hit Tulungagung Regency and caused considerable losses. From the results of the review, it becomes a parameter for researchers to offer pre-disaster mitigation programs in the form of providing posters containing disaster mitigation materials to communities in landslide-prone areas. The choice of poster media is because the information conveyed is easier to reach and understand by the public. In this study, researchers used a measurement tool in the form of a questionnaire that was distributed to 76 respondents so that initial understanding through Pretest and improvement after giving poster media through Posttest. The results of data analysis in which, the value of knowledge of the people who were respondents in this study was considered better and, in the Wilcoxon, test obtained a result of <0.05 showed that poster media is effective as a medium in supporting disaster preparedness in Tulungagung Regency